Beberapa Pikiran Mengenai Perkembangan Televisi di Indonesia - Iskandar Alisjahbana; Baidillah Mardjuni (Institute for Research and Community Services (LPPM) ITB, 1964)
Ichtisar. Televisi, selain vital untuk bangsa2 NEFO guna memperkuat persatuan dan memperkembangkan kepribadiannja, djuga merupakan suatu keharusan jang mutlak untuk menghadapi tantangan2 jang disebabkan oleh kemadjuan2 teknik, chusus dalam bidang telekomunikasi. Dengan kemadjuan2 jang ditjapai dalam Space radio2 communication, jaitu hubungan radio melalui satelit buatan jang diorbitkan diangkasa luar, dalam waktu jang tidak terlalu lama, dapat diramalkan bahwa tiap penduduk dibumi ini, tidak hanja dapat menerima siaran2 radio, tetapi djuga dapat mengikuti siaran2 televisi dari tiap negara diseluruh dunia. Untuk menghadapi tantangan ini, Indonesia tidak dapat tergantung hanja dari djaringan2 telekomunikasi jang dibangun melulu dengan alat2 buatan luar negeri. Tulisan ini menjarankan suatu djaringan alternatip jang sederhana dan murah, dimana potensi industri dalam negeri jang ada, sudah dapat diikut sertakan. Djaringan alternatip ini berdasarkan suatu projek-teladan stasiun relay televise digunung Tangkubanprahu untuk penerimaan dikota Bandung, jang merupakan hasil karja Panitia Transmisi Televisi Eksperimentil. Sedikit perhitungan jang merupakan dasar dari projek-teladan di Tangkubanprahu ini, diuraikan sekadarnja. Abstract. Television is vital to the New Emerging Forces nations, and is also a means of strengthening their unity and developing their integrity. Television is also important to a nation facing the challenge of modern technical development, particularly in the field of telecommunication. With the advances achieved in Space-Radio Communication, that is radio communication through manmade satellites orbited into outer space, it can be predicted that in the near future, people on earth will not only be able to receive radio broadcasts, but also to watch programs from every country in the world. To face this challenge, Indonesia, in setting up her telecommunication network, must not depend on foreign made instruments. This paper suggests an alternative and less expensive telecommunication network in which potential domestic industries are able to participate. This alternative network is based on a pilot project television relay station on Mount Tangkubanperahu for reception in the Bandung area. This pilot project is the work of the Committee on Television Experimentation. A few basic computation on which the Tangkubanperahu pilot project is based are demonstrated. The proposed television network, are taking advantages of high mountains which are a feature of Indonesian landscape; unfortunately a complete survey has not yet been made. The use of high mountains, however, has logistic consequences, and further study of this aspect is necessary.